Ferric carboxymaltose: choice of treatment in postpartum anaemia in multispeciality zonal hospital of armed forces medical services - Borse, Dhananjay S.; Mitra, Binay; Maji, Debkalyan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: World Health Organization has defined postpartum anemia (PPA) as hemoglobin (Hb) of < 10 gm% during the postpartum period. The objective of the present study was to compare the safety and efficacy of ferric carboxymaltose (FCM) in the treatment of post-partum anaemia (PPA). Methods: A total of 214 patients were identified in a zonal hospital of Armed Forces Medical Services, between Jan 2019 and August 2019 who found to have PPA. Patients having hemoglobin (Hb) <10 g/dl were assigned to receive Intravenous FCM, as per the calculated dose. Changes in hemoglobin (Hb) and serum ferritin levels at 2 and 6 weeks after treatment were recorded and analyzed. Adverse effects to FCM administration were also recorded. Results: Significant rises in Hb and serum ferritin levels were observed. The mean increase in Hb after 2 weeks was 3.1±0.50 g/dl and 4.0±70 g/dl at 6 weeks. The mean increase in serum ferritin levels after 2 weeks was 210.40±38.50 and 270.25±14.60 ng/ml after 6 weeks. Adverse drug reactions were significantly less (p<0.001). Conclusions: Ferric carboxymaltose increases Hb level and restores iron stores faster without any severe adverse drug reactions. Patient tolerance was good after FCM injection.